Pengaruh Religiusitas, Kualitas Layanan dan Daya Tarik Model Fashion terhadap Minat Beli Konsumen di Kota Banjarbaru - Mindariani Mindariani; Akhmad Hulaify; SS. Purnamasari (STIKes Ibnu Sina Ajibarang, 2025)
This research is motivated by an existing phenomenon where the level of religiosity related to the way people dress today causes people to dress in a closed manner in accordance with sharia. There is a decline in buying interest at this time, due to the increasingly fierce competition in the Muslim fashion industry. Therefore, it is important to understand the factors that influence consumer purchasing decisions. Al-Qory Boutique takes advantage of religiosity, quality of service and the attractiveness of fashion models to attract consumers to increase the purchase rate of its products in the form of fashion clothing trends. The formulation of the problem from this study is whether religiosity, service quality and the attractiveness of fashion models affect the buying interest of consumers in the city of Banjarbaru. The purpose of the study is to determine the impact of religiosity on consumer buying interest in Banjarbaru City, to find out the impact of service quality on consumer buying interest in Banjarbaru City, to find out the impact of fashion model attraction on consumer buying interest in Banjarbaru City. This study uses quantitative-descriptive research methods with a population of 258,753 people and a sample of 100 people. The data analysis used in this study is multiple linear regression using SPSS version 25. The results of the study showed that the three independent variables, namely religiosity, service quality, and attractiveness of fashion models, had a significant effect on consumer buying interest. Religiosity has a significant influence with a regression coefficient value of 0.257 and a p-value of 0.042. The quality of service also had a significant effect with a regression coefficient value of 0.207 and a p-value of 0.021. The attractiveness of fashion models shows the most dominant influence with a regression coefficient value of 0.463 and a p-value of 0.000.